2003
DOI: 10.1007/s00394-003-0409-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of catecholamines and potassium, and heart rate during exercise testing in obese subjects

Abstract: During physical exercise K(+) and catecholamines kinetics differ significantly in obese subjects vs normals and they may justify a less prompt cardiac response at the higher work-loads and a lower work capacity. The present data can be interpreted in the light of the insulin resistance syndrome of obesity, which causes an abnormal regulation of the Na-KATPase and of K(+) channels during physical exercise. The results of the present study may be relevant to nutritionists when suggesting physical exercise to obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Hypertrophy may depend on an increased amount of work that is required to move heavier bodies. In agreement with data from a previous study [26], lower maximal plasma K + levels were observed in the obese subjects during maximal exercise. It is conceivable that a difference of K + , if any, should be in the opposite direction than that observed, due to the larger muscular mass of obese subjects releasing K + (increased FFM, higher values of creatine kinase [27]).…”
Section: Discussionsupporting
confidence: 82%
“…Hypertrophy may depend on an increased amount of work that is required to move heavier bodies. In agreement with data from a previous study [26], lower maximal plasma K + levels were observed in the obese subjects during maximal exercise. It is conceivable that a difference of K + , if any, should be in the opposite direction than that observed, due to the larger muscular mass of obese subjects releasing K + (increased FFM, higher values of creatine kinase [27]).…”
Section: Discussionsupporting
confidence: 82%
“…36 On the other hand, other studies show that although many obese individuals have normal "resting" levels of NE, they exhibit significant differences in NE induction following stress. 37 In addition, obesity has been associated with cellular resistance to NE and other adrenergic agonists. 38 In some tissues, this is due to decreased adrenoceptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Others have described higher resting heart rate but decreased maximal heart rate in overweight adults, 38,40 which may be attributable to decreased maximal catecholamine responses. 21,41 To our knowledge, this is the first report of a significant relationship between HRR and fitness and performance in overweight adolescents. Additional study, including detailed measurement of cardiac function, is needed to clarify whether cardiac impairment (or the initial stages of impairment) may exist in severely overweight adolescents.…”
Section: E694mentioning
confidence: 99%
“…Other reports have suggested that both deconditioning and obesity may reduce maximal heart rate. 21,27,39,40,41 Because of their higher resting heart rate and lower maximal …”
mentioning
confidence: 99%